Global Specification and Validation of Embedded Systems Integrating Heterogeneous Components - Nicolescu, G.; Jerraya, A. A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
Global modelling and validation is required to master the design of systems made of heterogeneous components. These systems are now omnipresent in our life, and they may be found in several domains such as communications (ex. mobile terminals, optical switches), health (e.g. cardiac stimulators, cochlear implants), transportation (ex. automotive and aeronautical), etc. The main difficulties for their design are modelling and validation of the interactions between different components (hardware, software, analogue, RF, optical and micro-mechanical). Global Specification and Validation of Embedded Systems offers a deep understanding of concepts and practices behind the composition of heterogeneous components. After the analysis of existing computation and execution models used for the specification and validation of different sub-systems, the book introduces a systematic approach to build an execution model for systems composed of heterogeneous components. Mixed continuous/discrete and hardware/software systems will be used to illustrate these concepts. The benefit of reading this book is to give a clear vision on the theory and practice of specification and validation of complex modern systems. The examples give to the designers solutions applicable in their daily practice.
Heterogeneous Systems Modeling: Basic Concepts -- Execution Models -- Heterogeneous Systems Validation Based on Execution Models -- Anatomy of a Hardware/Software Execution Model in Heterogeneous Systems -- Anatomy of a Continuous/Discrete System Execution Model for Timed Execution of Heterogeneous Systems -- Methodology for Heterogeneous Systems Validation.
Keywords: ENGINEERING; SOFTWARE ENGINEERING; INFORMATION THEORY; COMPUTER SIMULATION; COMPUTER AIDED DESIGN; SYSTEMS ENGINEERING; ENGINEERING; CIRCUITS AND SYSTEMS; COMPUTER-AIDED ENGINEERING (CAD, CAE) AND DESIGN; SIMULATION AND MODELING; THEORY OF COMPUTATION; SPECIAL PURPOSE AND APPLICATION-BASED SYSTEMS